Pentecostal theology and ecumenical theology : interpretations and intersections - Hocken, Peter; Richie, Tony; Stephenson, Christopher A. (Global Pentecostal and Charismatic studies, 2019)
"Pentecostal Theology and Ecumenical Theology: Interpretations, Intersections, and Inspirations brings together globally recognized and newer scholars to address the complex relationship between Pentecostalism and the Ecumenical Movement. Historical essays address topics such as early Pentecostal responses to and participation in ecumenism, explicit convergences between Pentecostal and ecumenical initiatives, and the particular contributions of Pentecostals and ecumenists outside North America and Europe. Constructive theological essays address intersections between ecumenical theology and systematic loci in Pentecostal perspective, in the hope that mutual exchange and criticism will lead to ways to improve both. Never before have this many scholars of Pentecostalism combined their efforts in order to focus on the relationship between Pentecostal theology and ecumenical theology past, present, and future"--